Trifocal assessment of responsibilities and tasks of home economics graduates in government programs - Macarayan, Nerissa Almiranez A.
The general objective of this study was to assess the responsibilities and tasks of home economics (H.E.) graduates employed by the government in Regions X, XI, and XII. Specifically, it sought to determine the actual responsibilities and tasks of graduates in teaching and extension work, compare their actual responsibilities and tasks with those expected of them by their employers and H.E. professors, compare the responsibilities and tasks of H.E. graduates as as expected by their employers and H.E. professors and determine the reasons why the graduates do not perform certain tasks. There were 79 home economics teachers, 51 extension workers, 75 employers of extension workers and 27 H.E. professors who participated in this study. Structured survey questionnaires were used by the researcher. In addition, interviews were made. The statistical test used were the Z test of proportion and Z test for the difference between two proportions. The findings revealed that the H.E. teachers were performing eight responsibilities and 67 tasks. These responsibilities were planning of teaching-learning activities, presenting subject matter/instructing, managing classroom, maintaining superior and co-teacher relations, enhancing one's profession, maintaining parent and community relations, non-formal teaching of adults and youth and managing the school lunch counter/canteen. They did not perform research. The extension workers were performing seven responsibilities and 24 tasks. These responsibilities were planning, implementing and documenting programs/projects, monitoring programs/projects, evaluating programs/projects and enhancing one's profession. They did not have responsibilities in the areas of identifying problems, researching, budgeting and accounting of funds. Significant differences were observed between the actual responsibilities and tasks of H.E. teachers and those expected by their employers in 72 tasks. There were significant differences between the actual tasks of extension workers and those expected by their employers in 39 tasks. There were also significant differences in actual responsibilities and tasks of H.E. teachers and extension workers and those expected by their H.E. professors. The main reason of the H.E. teachers and extension workers for not performing some tasks expected of them were lack of knowledge and skills in doing the tasks, lack of awareness that they have the tasks and lack of resources. Revision of the present BSHE curricula in the universities in this study is recommended to include courses that will prepare the graduates for responsibilities and tasks that will enable them to perform their tasks in teaching and extension services in government programs. Other recommendations are proper orientation of H.E. graduates, faculty members and employers, better supervision and regular in-service training.